Financial Literacy and Financial Attitudes: The Role of Student Demographics - Sriwidharmanely, Sriwidharmanely; Cinda Syah Putri Bangun; Badani Hatta; Danang Adi Putra; Agus Rahmat (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to determine whether understanding financial literacy or vice versa influences the financial management attitude of accounting students. The research sample consists of USU and UNIB accounting students from the 2020-2023 batch. Data is collected using a questionnaire through the media (Google Forms) and distributed online. The questionnaire includes several measurement indicators representing understanding of financial literacy, such as investment, savings, and loans. The test involved multiple regression analysis. The analysis was conducted by separating samples from Medan and Bengkulu. The study results indicate that understanding financial literacy influences financial management attitudes. Furthermore, additional testing was carried out by analyzing financial literacy indicators, It was found that the financial literacy indicators in this study were significant and influential. This result demonstrates the overall contribution of these indicators to the significant impact of financial literacy understanding on the financial management attitude of accounting students.